Melanosis tubae et ovarii: An overlooked entity? - Ashutosh Rath; Bhagyashree Priyadarshini; Varuna Mallya; Nita Khurana; Anjali Tempe (Wolters Kluwer Medknow Publications, 2022)
Melanosis is a rare benign entity defined by the deposition of brownish-black pigment in a wide variety of organs especially the gastrointestinal tract, peritoneum, fallopian tubes and ovaries. Melanosis of the fallopian tube is widely known as pigmentosis tubae. Literature has mentioned ovarian teratomas and serous cystadenomas to be associated with the ovarian and peritoneal melanosis. We report five such cases of tubo-ovarian melanosis. The cases include mature teratoma and serous cystadenoma as well as melanosis of the fallopian tubes with otherwise normal ovarian histology. The importance of recognising this entity lies in its differential diagnosis.